Pengaruh Edukasi Kesehatan tentang Prosedur Operasi Sectio Cesaria (SC) terhadap Tingkat Kecemasan pada Pasien Pre Operasi Sectio Cesaria : Impact of Health Education Regarding Cesarean Procedures on Preoperative Anxiety Levels in Cesarean Section Patients - Nurwanto; Yeni Rusyani; Dwi Puji Susanti (Jurnal Keperawatan Berbudaya Sehat, 2026)
Caesarean section (CS) delivery is increasing globally. Based on Survei Kesehatan Indoneisa data, on 2023 the CS delivery rate was at 25,9%, with an increasing trend from year to year. The impact of the decision to take pre-operative CS is a stressor for patients that can trigger stress reactions both physiologically and psychologically. Psychological responses can be anxiety. Handling anxiety in pre-op-CS patients is very important to prevent various serious negative impacts, both on physical and mental health. Preoperative education plays a role in reducing anxiety by 58%. clear and comprehensive education about surgical procedures can help reduce uncertainty and anxiety. This study is a type of pre-experimental designs with one group pretest and posttest. The population in this study were patients giving birth with CS at RSU Fastabiq Pati. The sampling technique with a total sampling of 30 patients. Measurement of anxiety using the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data processing using SPSS with a computer with univariate and bivariate analysis using the Wilcoxon statistical test. The results of the study proved that statistically there was a difference in the level of anxiety before and after health education about the Sectio Cecarea surgical procedure, as evidenced by a p value of 0.000 (<0.05). There is an influence of health education about the CS surgical procedure on the level of anxiety in pre-op CS patients at Fastabiq Hospital.